The Role of Cue Utilization during a Simulated Driving Scenario. (November 2019) - Sturman, Daniel; Wiggins, Mark W.
The present study was designed to establish whether a cue-based assessment of driving could predict cognitive load and performance during a simulated driving task. Following an assessment of cue utilization in the domain of driving, participants completed a moderate workload simulated driving task, during which cerebral oxygenation, eye behavior, and driving performance metrics were recorded. During the simulated driving task, participants with higher cue utilization recorded smaller increases in cerebral oxygenation in the prefrontal cortex relative to baseline, and smaller mean fixation dispersions, compared to participants with lower cue utilization. There were no statistically significant differences in the number of speed exceedances nor missed traffic signals based on cue utilization. These outcomes suggest that participants with higher cue utilization were able to allocate fewer cognitive resources to the simulated driving task, while maintaining an equivalent level of driving performance, compared to participants with lower cue utilization.